Welfare and social protection in contemporary Latin America - Cruz-Martínez, Gibrán (Routledge studies in Latin American development, 2019)
Social protection serves as an important development tool, helping to alleviate deprivation, reduce social risks, raise household income and develop human capital. This book brings together an interdisciplinary team of international experts to analyse social protection systems and welfare regimes across contemporary Latin America. The book starts with a section tracking the expansion of social assistance and social insurance in Latin America through the state-led development era, the neoliberal era and the pink-tide. The second section explores the role played by local and external actors modelling social policy in the region. The third and final section addresses a variety of contemporary debates and challenges around social protection and welfare in the region, such as gender roles and the empowerment of CCT beneficiaries, and welfare provision for rural outsiders. The book touches on key topics such as conditional cash transfer programmes, trade union inclusionary strategies, transnational social policy, state-led versus market-led welfare provision, explanatory factors in the emerging dualism of social protection institutions, social citizenship rights as a consequence of changing social policy architecture and different poverty reduction strategies. This interdisciplinary volume will be of interest to economists, political scientists, sociologists, anthropologists and historians working on social protection in Latin America, or interested in welfare systems in the global south